Ruptured pulmonary hydatid cyst - masquerading as tuberculous pleural effusion in a child - Mishra, Rajeeva; Shankari, Vidhya (Indian Journal of Child Health, 2015)
We report a case of intrapleural rupture of hydatid cyst of the lung in a 12 year old female child who presented with a persistent cough since 3 years. She was misdiagnosed as tuberculous pleural effusion, which on contrast enhanced computed tomography thorax was diagnosed as ruptured hydatid cyst. She was treated conservatively and referred for further surgical correction. Following the surgical correction, the patient condition improved dramatically.